2020
DOI: 10.1080/13625187.2020.1743825
|View full text |Cite
|
Sign up to set email alerts
|

Slow implementation of mifepristone medical termination of pregnancy in Quebec, Canada: a qualitative investigation

Abstract: Objectives: Mifepristone for first-trimester medical termination of pregnancy (MTOP) became available in Quebec in 2018, one year after the rest of Canada. Using the theory of the Diffusion of Innovation (DOI) and the transtheoretical model of change (TTM), we investigated factors influencing the implementation of mifepristone MTOP in Quebec. Material and Methods: Semi-structured interviews were conducted with 37 Quebec physicians in early 2018. Deductive thematic analysis guided by the theory of DOI explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…From December 2020 to January 2021, we conducted the survey (UBC-CW REB, H16-01006), which included a consent form and questions assessing brief demographics, monthly MA volume from January to September 2020, previous experience providing MA via telemedicine, and the impact of the COVID-19 pandemic on the provision of abortion services (see Supplementary Data ). We excluded respondents practicing in Quebec from analysis of MA-related questions, as restrictive medical policies sustained providers’ preference for surgical abortion and provincial/administrative inertia limit access to MA ( 15 , 25 ). This survey was available in English and French and we invited members of the Canadian Abortion Providers Support—Communauté de pratique canadienne sur l’avortement network (a national community of practice to support mifepristone abortion practice) via registered email ( 10 , 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…From December 2020 to January 2021, we conducted the survey (UBC-CW REB, H16-01006), which included a consent form and questions assessing brief demographics, monthly MA volume from January to September 2020, previous experience providing MA via telemedicine, and the impact of the COVID-19 pandemic on the provision of abortion services (see Supplementary Data ). We excluded respondents practicing in Quebec from analysis of MA-related questions, as restrictive medical policies sustained providers’ preference for surgical abortion and provincial/administrative inertia limit access to MA ( 15 , 25 ). This survey was available in English and French and we invited members of the Canadian Abortion Providers Support—Communauté de pratique canadienne sur l’avortement network (a national community of practice to support mifepristone abortion practice) via registered email ( 10 , 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, Health Canada updated the product monograph and associated guidance to broaden eligibility to 63 days since the first day of the last menstrual period, expand prescribing authority, permit pharmacist dispensing, and allow individual clinicians to determine the need for an ultrasound [15][16]. As a result of these regulatory changes as well as the coverage of mifepristone/misoprostol by provincial and territorial health insurance schemes, medication abortion became increasingly accessible throughout most of the country [12][13][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…As medical abortion counselling may require additional time and resources inadequately reflected in a pharmacist's dispensing fee, our data indicate this may act as an additional barrier to provision for some pharmacists. Ongoing research 3,[32][33][34][35] suggests that 3 years since mifepristone/misoprostol for medical abortion entered the Canadian market in January 2017, uptake continues to be variable across Canada. Several pharmacy managers in our study reported using the Pharmacist Checklist and Resource Guide to train staff pharmacists for medical abortion provision. Indeed, a strength of our study was our integrated knowledge translation strategy for engaging knowledge users throughout the research process.…”
Section: Discussionmentioning
confidence: 99%
“…As medical abortion counselling may require additional time and resources inadequately reflected in a pharmacist’s dispensing fee, our data indicate this may act as an additional barrier to provision for some pharmacists. Ongoing research 3 , 32 - 35 suggests that 3 years since mifepristone/misoprostol for medical abortion entered the Canadian market in January 2017, uptake continues to be variable across Canada.…”
Section: Discussionmentioning
confidence: 99%